The Relationship Between Safety Climate, Employee Health and Job Satisfaction - Selvi, Rajamanickam (2012)
The main objective of this study is to investigate the relationship between safety climate, employee health and job satisfaction. It acesses the job satisfaction level of the construction building workers. The data is analyzed using Correlation. Data were obtained through questionnaire survey at MRCB construction projects in Kuala Lumpur. There were only 150 sets of questionnaires in each company were gathered and used for subsequent analyses. The survey only conducted in three consultants department and the number of questionaires limited to fifty per company. Provide additional evidence of construct validity. The result indicated that there is a significant relationship between safety climate and job satisfaction. The correlation that exists between safety climate and job satisfaction is positive and moderate.Using the statistical formula r(104) = 0.425, p< 0.01. The significant value is 0.006 where it is smaller than stated significant level 0.01. So, hypothesis null is failed to be accepted. Thus, it can be concluded that safety climate in the organization influence employee’s job satisfaction. The correlation that exists between the employee health and job satisfaction is positive and moderate. Using the statistical formula r (104) = 0.485, p< 0.01. The significant value is 0.007 where it is smaller than stated significant level 0.01. So, hypothesis null is failed to be accepted. Thus, it can be concluded that employee health give impact to the job satisfaction. The relationship that exists between employee health and job satisfaction is positive and moderate. It means that, excellent management of employee health may give job satisfaction to the workers.